Marhasnida : Lahirnya seorang Seniman dari Nagari Siguntur Sumatera Barat - Diana Putri Nengsi; Hendra Naldi (Jurnal Kronologi, 2022)
This research is in the form of a thematic biography that discusses the life journey of a Marhasnida as an activist in traditional dance. The existence of the figure of Marhasnida who played a major role in the original traditional dance of Nagari Siguntur made the dance develop to a national level. This study aims to explain the life journey of an artist from traditional dance from Nagari Siguntur. This research includes qualitative research using historical research methods consisting of four stages, namely (1) heuristics, namely collection of historical sources orally and in writing, (2) source criticism, (3) interpretation, namely the interpretation of historical evidence, (4) historiography, namely the writing of history in the form of scientific works. The results showed that Marhasnida was a figure who played a major role in reviving a long-lost traditional dance until it developed into a traditional dance that is known by many people and has reached the national level and has been invited to prestigious activities in every dance performance.